Comprehensive organometallic chemistry III - Mingos, D. M. P., 1944-; Crabtree, Robert H., 1948- (Elsevier, 2007)
Provides essential information for any chemist or technologist who needs to use or apply organometallic compounds. Provides a comprehensive overview of recent developments in the field and attempts to predict trends in the field over the next ten years.
Keywords: Organometallic chemistry.; Organometallic compounds.; elektronické knihy; electronic books